Applications of Synchrotron Light to Scattering and Diffraction in Materials and Life Sciences - Gomez, Marian.; Nogales, Aurora.; Garcia-Gutierrez, Mari Cruz.; Ezquerra, T.A. (Lecture Notes in Physics,, 2009)
The present set of lecture notes originates from the deeply felt need in the community to bridge the gap between beamline manuals and advanced graduate textbooks. The volume is a collection of tutorials, surveys and reviews. They cover most cases of relevance and interest where the combination of synchrotron light with various scattering and diffraction techniques is a very helpful approach to obtaining essential information about the structure of large molecular assemblies in low-ordered environments. Soft condensed matter and biomaterials, as well as complex fluids, are typical of the materials considered here. Contributions to this volume have been selected on the basis of their close relevance to advanced synchrotron radiation sources and state-of-the art beamline work.